2015
DOI: 10.1002/pros.22994
|View full text |Cite
|
Sign up to set email alerts
|

FGF19 promotes progression of prostate cancer

Abstract: FGF19 might be associated with biochemical recurrence after radical prostatectomy by promoting cell proliferation and epithelial-mesenchymal transition of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…However, a large body of research has demonstrated that this signaling axis is highly deregulated in numerous cancers, including amplification of FGFs in epithelial or stromal cells, and/or aberrant expression or activation of FGFRs resulting from genetic translocation, mutation, or amplification in tumorigenic cells (2). Pathological FGF/FGFRs signaling promotes crosstalk of tumorigenic cells with their microenvironment, which drives tumor proliferation, angiogenesis, and metastasis in cancer progression (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…However, a large body of research has demonstrated that this signaling axis is highly deregulated in numerous cancers, including amplification of FGFs in epithelial or stromal cells, and/or aberrant expression or activation of FGFRs resulting from genetic translocation, mutation, or amplification in tumorigenic cells (2). Pathological FGF/FGFRs signaling promotes crosstalk of tumorigenic cells with their microenvironment, which drives tumor proliferation, angiogenesis, and metastasis in cancer progression (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, amplification of the FGF19 gene has been identified as a frequent genetic aberration in HCC, prostate, breast, and lung squamous cancers . However, the clinical correlation of FGF19 gene amplification and the potential therapeutic effects of targeting FGF19 in LSCC are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, engineered forms of FGF19 which retain the ability to regulate bile acid metabolism but lack tumorigenicity have been reported [96,97]. However, induction of FGF19 has also been associated with the development and aggressiveness of other types of cancer including prostate [98,99] and colon cancer [100]. Therapeutic strategies to inhibit FGF19 function to reduce cancer progression have been proposed and should also be carefully evaluated.…”
Section: Metabolic Actions Of Fgf15/19mentioning
confidence: 99%